Male breast metastasis of ureteral cancer: a case report - Yoshitaka Ishikawa; Isao Tabei; Atsushi Fushimi; Azusa Fuke; Chikako Sekine; Tomoyoshi Okamoto; Hiroshi Takeyama (Surgical Case Reports)
Abstract Background Breast metastasis from extra-mammary primary tumors is extremely rare. We recently experienced a rare case of a male breast metastasis of ureteral cancer and will provide a case report. Case presentation A 74-year-old man developed a ureteral cancer and underwent left nephroureterectomy with lymph node dissection. Although enlarged abdominal lymph nodes did not disappear completely after chemoradiotherapy, further extensive therapy was not performed. A mass just below the nipple of his right breast was acknowledged and he visited our department. Histological diagnosis was invasive carcinoma. It was initially diagnosed as a primary breast cancer, and he underwent a mastectomy and a sentinel lymph node biopsy. There was no intraductal lesion and the border of the tumor was clear. It was very similar to that of the previous ureteral cancer. The final diagnosis was breast metastasis of ureteral cancer rather than primary breast cancer. The postoperative course was good, but multiple lung metastases appeared 2 months after surgery. He eventually died of cancerous lymphangiopathy. Conclusion It is important to accurately diagnose primary breast cancer or breast metastasis so as not to cause extra-invasion, but it was considered difficult to make a complete preoperative diagnosis.